Українці Румунії: етнокультурна історія і сучасний стан - Рендюк, Т. (Народна творчість та етнологія, 2019)
Проаналізовано історичні аспекти, пов’язані з появою предків українців на території сучасної Румунії. Достеменно доведено, що значна частина українців Румунії є автохтонним населенням регіону. Водночас продемонстровано, що українці Добруджі та дельти Дунаю є нащадками запорізьких козаків, а ті, що проживають у Банаті (Захід Румунії), є переселенцями з території нинішньої Закарпатської області України. Наведено офіційну позицію румунської влади стосовно розподілу українського етносу на власне українців, русинів та гуцулів (як окремих національностей), що не відповідає дійсності й спростовано навіть самими румунськими вченими. Офіційне визнання Бухарестом русинів і гуцулів окремими етнічними групами – це ні що інше, як спроба штучного «розмивання» української громади країни, прагнення до її організаційного роздроблення та зменшення її ролі, потенціалу і питомої ваги в румунському суспільстві. Представлено як негативне явище процес стрімкого скорочення чисельності українців Румунії, що є наслідком їх послідовної асиміляції, та визначено завдання української сторони, спрямовані на збереження їх національної ідентичності. Historical aspects connected with the appearance of the Ukrainian ancestors on the territory of modern Romania are analyzed. It is proven, for certain, that the vast majority of Ukrainians in Romania are an autochthonous population with long-standing roots in the region. At the same time, it is demonstrated that the Ukrainians from Dobrogea and the Danube Delta are the descendants of the Zaporizhian Cossacks, living in Banat (West of Romania), the migrants from the territories of the modern Transcarpathian oblast of Ukraine. An official position of the Romanian authorities concerning the division of the Ukrainian ethnic group into Ukrainians themselves, Rusyns, and Hutsuls as separate nationalities, as one that is not consistent with reality, is shown, and it is emphasized that the Romanian scientists themselves have denied it. The official recognition of Rusyns and Hutsuls by Bucharest as separate ethnic groups from Ukrainians is nothing more than an attempt to artificially blur the Ukrainian community of Romania artificially, aspiration for its organizational fragmentation, and diminution of its significance, potential, and relative importance in Romanian society. The process of a swift reduction of a number of Ukrainians in Romania is presented as a negative phenomenon. It is a consequence of their consistent assimilation. The tasks of the Ukrainian side aimed at the preservation of their national identity are defined.